2013
DOI: 10.1111/cch.12048
|View full text |Cite
|
Sign up to set email alerts
|

I could never do that before’: effectiveness of a tailored Internet support intervention to increase the social participation of youth with disabilities

Abstract: The Internet could be a viable method to facilitate social participation for youth with disabilities. Youth identified the benefits of one-to-one support at home and training of the family compared with typical group training at school. Despite its success with this group of youth, the time and effort intensive nature of this approach may limit the viability of such programmes. Further longitudinal research should investigate whether Internet use is sustained post intervention, and to identify the factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 34 publications
5
64
0
11
Order By: Relevance
“…Within the current study, siblings were mentioned more frequently than parents as supporting social media use and some parents evidently found it difficult to find out about technology. This reinforces Raghavendra et al's [9] findings that there is great variability between families and friends in terms of technical knowledge and digital literacy abilities.…”
Section: Causal Conditions For Achieving the Core Categorysupporting
confidence: 85%
See 3 more Smart Citations
“…Within the current study, siblings were mentioned more frequently than parents as supporting social media use and some parents evidently found it difficult to find out about technology. This reinforces Raghavendra et al's [9] findings that there is great variability between families and friends in terms of technical knowledge and digital literacy abilities.…”
Section: Causal Conditions For Achieving the Core Categorysupporting
confidence: 85%
“…Many adolescents claim they could not live without the Internet and love how new technology helps them communicate with people [73], which is supported by Helseth and Misvaer [74] who found peer relationships were a psychosocial factor that adolescents used to evaluate their quality of life. Within the current study, the desire to use the Internet and social media (especially Facebook) was unanimously expressed amongst the participants and extends understanding from previously cited literature that people who use AAC perceive benefits for widening and clarifying communication with others through the use of mobile technologies [7][8][9][10][11][12][13][14].…”
Section: Core Category -The Desire To Use the Internet And Social Mediasupporting
confidence: 64%
See 2 more Smart Citations
“…Our own work and that of others has shown that Australians from lower income and disadvantaged backgrounds face challenges to using ICT in general, as well as for health purposes, and may need intensive support if they are to become the 'empowered consumers' envisioned by the E-Health Strategy (e.g. Goodall et al 2010;Newman et al 2010;Baum et al 2012;Raghavendra et al 2013;Wen et al 2011). Some studies of the effectiveness of e-health also show that benefits do not necessarily accrue as expected.…”
mentioning
confidence: 88%